Ensuring Safer Hospitals: Strategies For Effective Infection Control (The Review of Diabetic Studies, 2024)
BackgroundHealthcare-associated infections (HAIs) remain a leading cause of morbidity, mortality, and economic burden in hospitals worldwide, with higher prevalence in low- and middle-income countries due to gaps in adherence, infrastructure, and safety culture. Despite the proven efficacy of evidence-based infection prevention and control (IPC) measures like hand hygiene and device bundles, robust programs are essential for resilient health systems.​MethodsThis systematic review follows PRISMA 2020 guidelines, searching PubMed and other databases for studies on IPC strategies in hospitals using terms for HAIs, interventions, and outcomes. Eligible designs include trials, cohort studies, and time-series analyses, data extraction and bias assessment using standardized tools, with narrative synthesis of effectiveness across settings.​ResultsHAI rates vary globally (3-15%), driven by MDROs like MRSA and CRE; multimodal IPC reduces CLABSI/VAP/SSI by 50-90% in ICUs via WHO/CDC cores. Innovations like AI surveillance and UV disinfection enhance outcomes; barriers include workloads, addressed by PDSA cycles boosting compliance >80%.​ConclusionsStructured IPC programs with leadership, surveillance, and multimodal strategies ensure safer hospitals, scalable across resources; future focus on AI, genomics, and LMIC trials will combat AMR and gaps.​